Spatial variation in dissolved phosphorus and interactions with arsenic in response to changing redox conditions in floodplain aquifers of the Hetao Basin, Inner Mongolia. (1st February 2022) - Li, Yao; Yu, Chen; Zhao, Bo; Chen, Dou; Ye, Haolin; Nagel, Christiane; Shao, Wen; Oelmann, Yvonne; Neidhardt, Harald; Guo, Huaming
Highlights: P cycling in groundwater was tightly constrained by redox conditions. Under oxic/suboxic conditions, OM mineralization and mineral weathering mobilized P. Under anoxic conditions, Fe(III)-oxide reduction became dominant for P mobilization. In Fe(III) reducing conditions, Ca/Fe(II)-minerals served as a sink for dissolved P. In SO4 2− reducing conditions, Fe(II)-sulfides preferentially immobilized P over as. Abstract: Increasing numbers of studies have reported groundwater with naturally high phosphorous (P) and arsenic (As) concentrations, which can potentially threaten the environment and human health. However, the cycling of P and its interactions with As in groundwater under changing redox conditions remain largely unknown. In this study, 83 groundwater samples and 14 sediment samples were collected from the Hetao Basin, Inner Mongolia, for systematic hydrogeochemical investigation and complementary geochemical evaluation. The results showed that P cycling in floodplain aquifers was tightly constrained by redox conditions. Under oxic/suboxic conditions, mineralization of organic matter and weathering of P-bearing minerals were the two dominant processes that mobilized considerable amounts of P in groundwater. When redox conditions became reducing, Fe(III)-oxide reduction dominated, resulting in enrichment of both P and As in groundwater. In Fe(III)-reducing conditions, secondary Ca/Fe(II)-minerals might serve as an important sink for P. When redox conditions became SO4 2− -reducing, preferential adsorption and incorporation of P over As on Fe(II)-sulfides might constrain the As immobilization pathway, resulting in immediate retardation of P and hysteretic immobilization of As. This P-immobilization pathway in natural aquifers has not been described before. This study provides novel insights into P cycling and As enrichment in groundwater systems. Understanding the roles of Fe(II)- and S(-II)-minerals in the immobilization of and interaction between P and As in response to SO4 2− reduction may help to inspire effective in-situ remediation of contaminated groundwater, in which P and As coexist and remain mobile for decades or longer. Graphical abstract: Image, graphical abstract .